External competitiveness of EU candidate countries - Lucia Orszaghova; Li Savelin; Willem Schudel (European Central Bank (ECB), 2013)
As the current financial crisis has shown, macroeconomic imbalances such as persistent current account and trade deficits, can seriously undermine a country's resilience to economic shocks. Maintaining and enhancing external competitiveness has thus become of increasing concern, particularly to European Union (EU) candidate countries whose economic growth models have been challenged in recent years. Drawing on previous studies, this paper assesses developments in the external competitiveness of EU candidate countries between 1999 and 2011. Taking a broad approach to the issue of competitiveness, the paper considers various indicators of both short and long-term competitiveness, including those related to domestic prices and costs, export performance, and institutional and structural issues. In the context of EU integration, comparisons are drawn with developments in the EU12. We find that, during the pre-crisis period, all candidate countries experienced robust export market growth, but also suffered losses in price and cost competitiveness. In terms of export characteristics, progress has been heterogeneous and also fairly slow when compared with the EU12. All candidate countries have increased their number of export products and trading partners, but only a few have been able to export more complex products. As regards structural issues such as corruption and bureaucratic efficiency, all countries have performed quite poorly with the exception of Iceland.
Keywords: H3; H6; E6; G1; 330; EU candidate countries; export growth; export specialisation; external competitiveness; Exportwirtschaft; Internationaler Wettbewerb; EU-Mitgliedschaft